Graduate attributes: How some university students experience and learn them - Bitzer, E.; Withering, M. (South African Journal of Higher Education, 2020)
The voices of university students are often absent from academic discourses on the learning of graduate attributes (GAs). Such attributes are mostly constructed and conceptualised from the viewpoint of academics, institutions, education authorities and industry. However, as students within democratic contexts are increasingly challenged to assume greater responsibility for their own growth and development, it seems imperative that they participate in discussions related to the acquiring of graduate attributes. This article reports on how students at one South African university understand and relate to graduate attributes. Data were generated from a group of students at the University of the Western Cape through focus group interviews and photo elicitation. The results indicate that students who understand what graduate attributes are and how they can acquire these attributes might enhance such students’ further growth and their employability.